Electronic storage capacity of ceria: role of peroxide in Aux supported on CeO2(111) facet and CO adsorption. Issue 41 (5th October 2015) - Liu, Yinli; Li, Huiying; Yu, Jun; Mao, Dongsen; Lu, Guanzhong
Abstract : Au adsorbs on CeO2 (111) with an O vacancy to form Au δ −, which is not favorable for CO adsorption. After peroxide formed on CeO2 (111) with an O vacancy, Au is oxidized to Au δ +, which improves CO adsorption on Au/CeO2, where CeO2 acts as an electron buffer. Abstract : Density functional theory (DFT+U) was used to study the adsorption of Au x ( x = 1–4) clusters on the defective CeO2 (111) facet and CO adsorption on the corresponding Au x /CeO2− x catalyst, in this work Au x clusters are adsorbed onto the CeO2− x + superoxide/peroxide surface. When Au1 is supported on the CeO2 (111) facet with an O vacancy, the strong electronegative Au δ − formed is not favorable for CO adsorption. When peroxide is adsorbed on the CeO2 (111) facet with the O vacancy, Au x was oxidized, resulting in stable Au x adsorption on the defective ceria surface with peroxide, which promotes CO adsorption on the Au x /CeO2− x catalyst. With more Au atoms in supported Au x clusters, CO adsorption on this surface becomes stronger. During both the Au being supported on CeO2− x and CO being adsorbed on Au x /CeO2− x, CeO2 acts as an electron buffer that can store/release the electrons. These results provide a scientific understanding for the development of high-performance rare earth catalytic materials.